2011
DOI: 10.1099/vir.0.029447-0
|View full text |Cite
|
Sign up to set email alerts
|

Charged amino acid patterns of coreceptor use in the major subtypes of human immunodeficiency virus type 1

Abstract: Human immunodeficiency virus type 1 has several genetic subtypes and two coreceptor use phenotypes: R5 that uses CCR5, while X4 uses CXCR4. A high amino acid charge of the envelope glycoprotein 120 V3 region, common at positions 11 and 25, is important for CXCR4 use. We characterized charged V3 amino acids, retrieving all biologically phenotyped sequences from the HIV Sequence Database. Selecting individually unique ones randomly yielded 48 subtype A, 231 B, 180 C, 37 D and 32 CRF01_AE sequences; 482 were R5 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…To date, several studies 12 14 36 37 38 39 40 have reported a key role of the V3 charge in coreceptor tropism. Improved performance has been observed by incorporating the V3 charge rule (11/25 rule and V3 net charge).…”
Section: Methodsmentioning
confidence: 99%
“…To date, several studies 12 14 36 37 38 39 40 have reported a key role of the V3 charge in coreceptor tropism. Improved performance has been observed by incorporating the V3 charge rule (11/25 rule and V3 net charge).…”
Section: Methodsmentioning
confidence: 99%
“…However, it remains to be determined how CXCR4-using HIV-1 without a positively charged amino acid at the 11th position of the V3 loop escapes from CXCR4 inhibitors. Since higher prevalence of CXCR4-using HIV-1 in CRF01_AE compared to subtype B has been reported [38], we first cloned and sequenced the env regions of HIV-1s from 21 CRF01_AE-infected individuals in a Japanese cohort to find CXCR4-using HIV-1 lacking positively charged amino acids at the 11th and 25th positions of the V3 loop. Among them, two out of five clones isolated from individual KI812 had a unique amino acid sequence (KI812.7) as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%